Entrepreneurs' transnational networks channelling exports: diasporas from Central & South America, Sub-Sahara Africa, Middle East & North Africa, Asia, and the European culture region. Issue 10 (26th July 2020) - Liu, Ye; Namatovu, Rebecca; Karadeniz, Emine Esra; Schøtt, Thomas; Minto-Coy, Indianna D.
ABSTRACT: Entrepreneurs located in the diaspora, compared to entrepreneurs located domestically, are well-known to export much, especially through transnational networking. This understanding has a gap: How is embeddedness of diasporic entrepreneurs in their origins shaping their transnational networking and trade? Globally representative samples of diasporic and domestic entrepreneurs have been surveyed, enabling comparisons of diasporas originating from the world's five regions: Central & South America, Sub-Sahara Africa, Middle East & North Africa, Asia, and the region of countries dominated by European culture. Entrepreneurs originating from European culture countries have larger transnational networks and more exports than entrepreneurs originating from any other region, particularly Sub-Sahara Africa. But diasporans from the other regions, especially Sub-Sahara Africa, have much larger transnational networks than their domestic peers. Transnational networking benefits exporting, in every location and every origin. Indeed, diasporans export more than domestics, by a direct effect and by additional indirect effects mediated through transnational networks, that differ across diasporas. By pioneering global comparisons of the diasporas from around the world, the study contributes to theorising by accounting for networking and trade, demonstrating that additional effects of being diasporan upon exporting are channelled through transnational networking, but differently across the heterogeneous diasporas.